The Establishment of Weak Ecological Microexpressions Recognition Test (WEMERT): An Extension on EMERT - Yin, Ming; Tian, Liangchen; Hua, Wei; Zhang, Jianxin; Liu, Dianzhi (Frontiers in Psychology, 2019)
The JACBART microexpression recognition test only examined the expression of facial expression under the neutral expression background, and the ecological validity was not high. The EMERT microexpression recognition test examined six mocroexpressions under seven background expressions, but did not detect the intensity of expressions. In this study, an weak ecological microexpressions recognition test WEMERT was established to examine the recognition features of six weak microexpressions in all seven high intensity basic expressions. The result found:(1)the test had good retest reliability, criterion validity and ecological validity. (2) The reliability and validity tests revealed a lot of characteristics of weakl microexpressions recognition. There were training effects in some weak microexpressions recognition. Weak microexpressions recognition were generally positively related to microexpressions recognition of JACBART, but were generally negatively related to approximate common expressions. The standard deviations of the accuracy of of the weak microexpressions in different background expressions were used to define the fluctuations of the weak microexpression recognition and we found that weak microexpressions recognition had many fluctuations. (3)Personality openness and its subdimensions were generaly positively related to some weak microexpression recognition, except that O1 was significantly negatively related to surprise under neutral.